Profitability, DuPont Framework, and Firm Value: Evidence from Indonesia’s Property and Real Estate Sector - Frandy Melvin Walean (Community Engagement and Emergence Journal (CEEJ), 2026)
This study examines whether profitability and its underlying drivers explain firm value in Indonesia’s property and real estate sector. Profitability is measured using Return on Assets, while Return on Equity is decomposed through the DuPont framework into Net Profit Margin, Total Asset Turnover, and the Equity Multiplier. Firm size, sales growth, and the current ratio are included as control variables. The study uses quantitative panel data from 35 property and real estate companies listed on the Indonesia Stock Exchange during 2018–2024, resulting in 245 firm-year observations. Data obtained from LSEG Refinitiv were analyzed using panel-data regression in EViews. The Chow and Hausman tests supported the use of the Random Effects Model. The findings show that the explanatory variables do not simultaneously have a significant effect on firm value, as measured by Tobin’s Q, and the model has limited explanatory power. Individually, ROA, net profit margin, firm size, and the current ratio are not significantly associated with firm value. Total Asset Turnover has a negative effect at the 10% significance level, while the Equity Multiplier has a negative effect at the 5% level. Sales growth has a positive effect at the 10% level. These results indicate that the DuPont components convey different valuation signals and that investors in this asset-intensive sector may respond more strongly to financing risk and growth prospects than to aggregate profitability measures. The study contributes to the firm-value literature by applying the DuPont framework to distinguish the operational and financing mechanisms underlying profitability. It also suggests that managers should align asset utilization and financing decisions with sustainable cash-flow and growth outcomes.